Randomized controlled trial of vertebroplasty versus kyphoplasty in the treatment of vertebral compression fractures. (24th June 2015) - Evans, Avery J; Kip, Kevin E; Brinjikji, Waleed; Layton, Kennith F; Jensen, Mary L; Gaughen, John R; Kallmes, David F
Abstract : Background: We present the results of a randomized controlled trial evaluating the efficacy of vertebroplasty versus kyphoplasty in treating vertebral body compression fractures. Methods: Patients with vertebral body compression fractures were randomly assigned to treatment with kyphoplasty or vertebroplasty. Primary endpoints were pain (0–10 scale) and disability assessed using the Roland–Morris Disability Questionnaire (RMDQ). Outcomes were assessed at 3 days, 1 month, 6 months, and 1 year following the procedure. Results: 115 subjects were enrolled in the trial with 59 (51.3%) randomly assigned to kyphoplasty and 56 (48.7%) assigned to vertebroplasty. Mean (SD) pain scores at baseline, 3 days, 30 days, and 1 year for kyphoplasty versus vertebroplasty were 7.4 (1.9) vs 7.9 (2.0), 4.1 (2.8) vs 3.7 (3.0), 3.4 (2.5) vs 3.6 (2.9), and 3.0 (2.8) vs 2.3 (2.6), respectively (p>0.05 at all time points). Mean (SD) RMDQ scores at baseline, 3 days, 30 days, 180 days, and 1 year were 17.3 (6.6) vs 16.3 (7.4), 11.8 (7.9) vs 10.9 (8.2), 8.6 (7.2) vs 8.8 (8.5), 7.9 (7.4) vs 7.3 (7.7), 7.5 (7.2) vs 6.7 (8.0), respectively (p>0.05 at all time points). For baseline to 12-month assessment in average pain and RMDQ scores, the standardized effect size between kyphoplasty and vertebroplasty was small at −0.36 (95% CI −1.02 to 0.31) and −0.04 (95% CI −1.68 to 1.60), respectively. Conclusions: Our study indicates that vertebroplasty and kyphoplasty appear to be equally effective in substantially reducing pain and disability in patients with vertebral body compression fractures. Trial registration number: NCT00279877.